Inhibitory effect of curcumin-artemisinin co-amorphous on Tau aggregation and Tau phosphorylation - Dubey, Tushar; Sonawane, Shweta Kishor; Mannava, M. K. Chaitanya; Nangia, Ashwini K.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Colloid and Surfaces B-Biointerfaces, 2023)
Tau is a natively unfolded microtubule-associated protein. Tau neurofibrillary tangles are one of the hallmarks of Alzheimer's disease. The post-translational modifications of Tau lead to its pathological state. Phosphorylation is the key post-translational modification associated with Tauopathy. Curcumin is a polyphenolic compound pre-sent in the rhizomes of Curcuma longa. Curcumin has been reported to have remarkable medicinal properties in several diseases, but its poor solubility limits its therapeutic potency. Artemisinin is a sesquiterpene lactone, which has been known sience ancient times for its applications as a treatment for various diseases such as malaria, cancer, autoimmune disease, etc. In the present study, the potency of crystalline curcumin, crystalline artemisinin, and Cur-Art co-amorphous dispersion were evaluated against Tau pathology. The in-vitro ThS/ANS fluorescence and electron microscopy results suggested that curcumin and Cur-Art efficiently inhibited Tau aggregation. Furthermore, exposure to curcumin and Cur-Art co-amorphous restored the impaired nuclear transport in formaldehyde-stressed cells. Curcumin was also found to modulate the phosphorylation of Tau, which indicated the neuroprotective potency. Thus, curcumin and Cur-Art co-amorphous exhibit therapeutic potential against Tau protein in Alzheimer's disease.
Keywords: artemisinin; curcumin; Phosphorylation; Tau Aggregation